The p12 domain is unstructured in a murine leukemia virus p12-CA(N) Gag construct. - Sampson K Kyere (Public Library of Science (PLoS), 2008)
The Gag polyproteins of gammaretroviruses contain a conserved p12 domain between MA and CA that plays critical roles in virus assembly, reverse transcription and nuclear integration. Here we show using nuclear magnetic resonance, that p12 is unstructured in a Moloney murine leukemia virus (MMLV) Gag fragment that includes the N-terminal domain of CA (p12-CA(N)). Furthermore, no long range interactions were observed between the domains, as has been previously predicted. Flexibility appears to be a common feature of Gag "late" domains required for virus release during budding. Residues near the N-terminus of CA(N) that form a beta-hairpin in the mature CA protein are unfolded in p12-CA(N), consistent with proposals that hairpin formation helps trigger capsid assembly.